The impact of interdisciplinary studies in administrative sciences on the requirements of the labor market in business administration – Case study of faculty members at Community College in Khamis Mushayt – - Ahamed, Rogaia Mohammed Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to identify the impact of interdisciplinary -studies on the future requirements of the labor market for the business administration specialization, and the correlational descriptive approach has been applied. A questionnaire was designed and distributed to the study sample consisting of 20 faculty members (case studies) of the faculty who specialize in business administration and they were from The most important results are the existence of a statistically significant relationship between the application of inter-studies in the business administration specialization and the compatibility of education outputs in the business administration specialization with the requirements of the future labor market. The gap between educational outcomes and labor market requirements.
Keywords: interdisciplinary studies; labor market requirements; faculty members; business administration